2015
DOI: 10.3389/fonc.2015.00069
|View full text |Cite
|
Sign up to set email alerts
|

Trailing TRAIL Resistance: Novel Targets for TRAIL Sensitization in Cancer Cells

Abstract: Resistance to chemotherapeutic drugs is the major hindrance in the successful cancer therapy. The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor (TNF) family of ligands, which initiates apoptosis in cancer cells through interaction with the death receptors DR4 and DR5. TRAIL is perceived as an attractive chemotherapeutic agent as it specifically targets cancer cells while sparing the normal cells. However, TRAIL therapy has a major limitation as a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 214 publications
3
187
0
Order By: Relevance
“…One of the most important aspects considered when designing therapeutic approaches using TRAIL receptor agonists is the diversity of mechanisms that can award resistance to TRAIL-mediated cell death (So et al, 2015; Trivedi & Mishra, 2015; Twomey et al, 2015). We have already mentioned the existence of the Decoy Receptors (DcR1/TRAIL-R3, DcR2/TRAIL-R4 and OPG), which can bind to TRAIL but are unable to activate either the apoptotic or necroptotic signaling cascade.…”
Section: Resistance To Trail—mediated Cell Deathmentioning
confidence: 99%
“…One of the most important aspects considered when designing therapeutic approaches using TRAIL receptor agonists is the diversity of mechanisms that can award resistance to TRAIL-mediated cell death (So et al, 2015; Trivedi & Mishra, 2015; Twomey et al, 2015). We have already mentioned the existence of the Decoy Receptors (DcR1/TRAIL-R3, DcR2/TRAIL-R4 and OPG), which can bind to TRAIL but are unable to activate either the apoptotic or necroptotic signaling cascade.…”
Section: Resistance To Trail—mediated Cell Deathmentioning
confidence: 99%
“…To ameliorate TRAIL activity, several formulations of recombinant TRAIL, such as fusion to poly-histidine, Flag and leucin Zipper tags, or linked to Fc portion of IgG, have been developed and are currently tested at preclinical level (6,7). The combination of recombinant TRAIL with chemotherapeutics, radiotherapy, small molecules, or natural compounds aimed at enhancing the sensitivity of cancer cells, have also found wide application in preclinical approaches (8,9). In addition, liposomes, mesenchymal stem cells, leukocytes, or engineered CD34…”
Section: Introductionmentioning
confidence: 99%
“…7 Accordingly, tremendous efforts have been made to clarify the mechanisms responsible for the resistance to TRAIL, and development of TRAIL-based combinatorial approaches is considered to be one of the most promising therapeutic strategies for cancer treatment. 8,33,34 In this study, we investigated whether AuNPs could modulate TRAIL sensitivity in NSCLC in vitro and in vivo toward the goal of providing new therapeutic options to treat refractory NSCLC. Here, we demonstrated that AuNPs enhance TRAIL-induced apoptosis in NSCLC by modulating mitochondrial dynamics, and TRAIL combined with AuNPs performs as an effective chemotherapeutic strategy for NSCLC.…”
Section: Discussionmentioning
confidence: 99%